The little encyclopedia of herbal medicine : 100 common remedies for everyday ailments - Renzetti, Angela (Sasquatch Books, 2025)
"Common Herbal Remedies for Everyday Ailments is your go-to reference for classic alternatives to over-the-counter medicine. This handy collection of herbal remedies is organized alphabetically by the name of each ailment, so you can quickly look up the herbal remedies you need. Featuring 50 common herbs that are available throughout North America, and packed with illustrations of each plant and its active ingredient, this indispensable resource makes it easy to use herbal remedies around the home"-- Provided by publisher.